You are Here: Home

# Simultaneous equations watch

1. (x+y)^2 = 4
2y - x = 0

what do you get?
2. (Original post by mik1a)
(x+y)^2 = 4
2y - x = 0

what do you get?
2y-x = 0 => x=2y

So, (3y)^2 = 4

9y^2 = 4

y^2 = 4/9

y = 2/3 or y = -2/3

y=2/3, x=4/3

y=-2/3, x=-4/3
3. (Original post by mik1a)
(x+y)^2 = 4
2y - x = 0

what do you get?
basically to make those easy, you just have to rearrange and subsititue in for x or y
4. that seems really obvious now thanks... i did it some other way and got 1/3, -1/3 2/3, -2/3 :s got to make less errors...
5. (Original post by mik1a)
that seems really obvious now thanks... i did it some other way and got 1/3, -1/3 2/3, -2/3 :s got to make less errors...
fewer errors not less :-)
6. lol rub it in

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: February 28, 2004
Today on TSR

### Edexcel C4 Maths Unofficial Markscheme

Find out how you've done here

### 2,210

students online now

Exam discussions

### Find your exam discussion here

Poll

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE